Design and Development of Variable Fiber Optic Coupler - Hanafi, Marsyita (2006)
This thesis presents the research works on design, development and analysis of variable fiber optic coupler. The fiber couplers are devices that distribute light from a main fiber into one or more branches of fibers which can be used as a power divider, wavelength-division multiplexer (WDM) and optical switches. These couplers are important in all fiber optic networks as they are used in long haul, metro, distribution and access fiber networks. With the widely increasing deployment of metropolitan area network, fiberto- the-home (FTTH) and cable TV networks, the market potential for the fiber couplers is becoming larger. However, most of the fiber couplers can only provide a fixed optical coupling ratio which is unable to provide flexibility, reliability and scalability. The evolution of the telecommunications networks has created an increasing demand for the variable fiber couplers, but there are some limitations of the existing variable fiber couplers such as unstable, small tuning range of coupling ratio, high in loss and costly. Hence, this gives rise to the need for searching new design of developing better performance variable fiber couplers. The new design utilize a fix coupling ratio Fused Biconical Tapered (FBT) coupler that is involved low loss coupling process and low in cost. This coupler is known as a Variable Fiber Optic Coupler (VFOC). There are two approaches used in this thesis that are simulation and experimentation. The simulation is important in designing the VFOCs, as through the simulation process, the characteristic of the design VFOCs can be determined. The successful simulation is then realized through the experimentation, which is included the fabrication of the VFOCs. However, the results obtained from the experiments are slightly different from the simulation results. These are due to the losses in the experiments and the ideal environment in the simulation. In the experiment, the variable coupling ratio is achieved by applying deflection to the fabricated FBT couplers. The dependency of the variable coupling ratio on the deflection is elaborated. It is found that in the range of 0.8 mm deflection, the coupling ratio can be varied from 11% to 92% with the excess loss less than 0.1 dB.